Efficacy of Probiotics Compared to Chlorhexidine Mouthwash in Improving Periodontal Status: A Systematic Review and Meta-Analysis. (23rd January 2023) - Henrique Soares, Kaio; Firoozi, Parsa; Maria de Souza, Glaciele; Beatriz Lopes Martins, Olga; Gabriel Moreira Falci, Saulo; Rocha dos Santos, Cassio Roberto
Abstract : Purpose . To critically evaluate the available literature and conduct a systematic review of recent randomized controlled trials to assess the effectiveness of probiotics compared to chlorhexidine mouthwash in enhancing periodontal health. Methods . Five databases were searched electronically, as well as the gray literature. Using the Cochrane risk-of-bias tool for randomized clinical trials, the risk of bias was examined. The weighted mean difference (WMD) method was used to calculate the effect sizes. Heterogeneity was assessed using I 2 and τ 2 statistics. The GRADE approach was adopted to assess the certainty of the evidence. To assess the robustness of the findings, sensitivity analysis and publication bias assessment were undertaken. Results . A total of 1850 studies were initially identified. Sixteen clinical trials were eligible for qualitative synthesis, and ten were included in the meta-analysis. In terms of the gingival index, in total, no statistically significant difference was observed between chlorhexidine and probiotics within 4 weeks (WMD −0.03, 95% CI: −0.09∼0.04, P  = 0.3885). Similar to GI, no statistically significant difference was observed between chlorhexidine and probiotics regarding the plaque index within 4 weeks (WMD 0.11, 95% CI: −0.05∼0.28, P  = 0.1726). No statistically significant difference was observed between chlorhexidine and probiotics in all time intervals regarding oral hygiene index-simplified (WMD −0.01, 95% CI: −0.05∼0.04, P  = 0.7508). The robustness of these findings was confirmed by sensitivity analysis and publication bias assessments. Conclusions . Based on the findings, probiotics were an acceptable alternative to conventional chlorhexidine in improving periodontal health. High-quality studies with rigorous methodology should be conducted to assess the optimum doses of probiotics for clinical implications.